2016
DOI: 10.1093/brain/awv387
|View full text |Cite
|
Sign up to set email alerts
|

On the right side? A longitudinal study of left- versus right-lateralized semantic dementia

Abstract: The typical presentation of semantic dementia is associated with marked, left predominant anterior temporal lobe atrophy and with changes in language. About 30% of individuals, however, present with predominant right anterior temporal lobe atrophy, usually accompanied by behavioural changes and prosopagnosia. Here, we aimed to establish whether these initially distinct clinical presentations evolve into a similar syndrome at the neural and behavioural level. Thirty-one patients who presented with predominant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
182
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 189 publications
(198 citation statements)
references
References 73 publications
14
182
2
Order By: Relevance
“…This may relate to early misdiagnosis of right temporal cases (see Discussion). We also observed evidence of asymmetric spread of atrophy to posterior temporal regions (Brambati, Rankin, et al, 2009; Kumfor et al, 2016; Rohrer et al, 2009). The L-svPPA group, on average, exhibited 22.3% volume loss in the left cTL (range = 0–36%) and 4.3% in the right cTL (0–16%).…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…This may relate to early misdiagnosis of right temporal cases (see Discussion). We also observed evidence of asymmetric spread of atrophy to posterior temporal regions (Brambati, Rankin, et al, 2009; Kumfor et al, 2016; Rohrer et al, 2009). The L-svPPA group, on average, exhibited 22.3% volume loss in the left cTL (range = 0–36%) and 4.3% in the right cTL (0–16%).…”
Section: Resultsmentioning
confidence: 53%
“…At initial clinical presentation, atrophy is typically bilateral though usually asymmetric with more extensive left hemisphere involvement. Over time, atrophy spreads through the initially less affected contralateral rostral temporal cortex and also to ipsilateral ventromedial frontal, insular and infero-posterior temporal regions (Brambati, Rankin, et al, 2009; Kumfor et al, 2016; Rogalski et al, 2014). Less frequently (approximately 30% of cases), patients present with greater right than left rostral temporal involvement.…”
Section: Introductionmentioning
confidence: 99%
“…For patients in the earlier stages of disease, this may have impacted on their clinical presentation, with right-sided patients exhibiting worse behavioural symptoms than patients with predominantly left-sided temporal lobe atrophy. With progression, however, the clinical profile of these subtypes becomes similar as left-sided svPPA also exhibit behavioural symptoms [25,26]. Paradoxically, semantic deficits appear not to be a main contributing factor to functional decline, given that they appear very early in the disease and at a time when ADL function is very well preserved.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a longitudinal cohort, however, demonstrates that those cases develop marked language deficits, demonstrating that irrespective of the initial clinical presentation, all sv-PPA cases evolve into a similar syndrome at the neural and behavioral level. 45 This convergent clinical progression shows not only the common nosology in both sv-PPA presentations, but it also suggests the relevance of observing the clinical trajectory to refining diagnosis. Of clinical importance, unlike other variants, almost all cases with sv-PPA develop some degree of behavioral symptoms such as agitation and delusions that can become disruptive and require pharmacological intervention.…”
Section: Associated Symptomsmentioning
confidence: 81%
“…43,44 Longitudinal studies in the other variants, in contrast, have demonstrated that sv-PPA presents the slowest rate of progression and semantic disintegration remains the most salient deficit and declines in a fairly stereotyped manner. 41,45,46 Similarly, expressive language deficits in nfv-PPA remains the most salient clinical problem, and before other linguistic deficits become prominent, extrapyramidal deficits often emerge. 47,48 The widespread and heterogeneous clinical involvement in lv-PPA has been the main motivation to suggest that this variant should be excluded from the spectrum of PPA presentations.…”
Section: Is Ppa a Unitary Syndrome Or An Artificial Conjunction Of DImentioning
confidence: 99%